Alternative models of Deliberative Democracy. An ap?proach toward the state of the art (2010)
Deliberative democracy, the concept that comes from the models of constitutional democracy and discursive democracy, defended respectively by Rawls Habermas, is confronted lately by several critical reactions that make more radical its alternative project